National Survey on the Management of Adult Bronchiectasis in Belgium. (2nd January 2019) - Schoovaerts, K.; Lorent, N.; Goeminne, P.; Aliberti, S.; Dupont, L.
Abstract: The increasing prevalence and incidence of bronchiectasis leads to a substantial health care burden. Quality standards for the management of bronchiectasis were formulated by the British Thoracic Society following publication of guidelines in 2010. They can be used as a benchmark for quality of care. It is, however, unclear how and whether they apply outside of the UK. Between May and November 2017, we conducted an online survey among respiratory physicians caring for adult bronchiectasis patients in Belgium. About 186 cases were submitted by 117 treating physicians. Patients were mostly female (58%), of Caucasian descent (84%) with a remarkably low median age of 59.8 (IQR 47–73) years. 41% had Pseudomonas aeruginosa, methicillin-resistant Staphylococcus aureus and/or Enterobacteriaceae isolated from respiratory samples in the past. 21% had three or more exacerbations, however, more than 58% were receiving long-term oral antibiotics (of which 90% azithromycin). In 40% of patients the diagnostic testing was insufficient. Surveillance of sputum bacteriology in stable patients and composing a self-management plan was missing in 53% and 68% of patients, respectively. Airway clearance techniques were implemented in 84%. Respiratory physicians complied with 60% or more to five out of the eight applicable quality standards, which is encouraging. Increasing educational act could further raise awareness and increase quality of care.